Program to evaluate microbial communities using sequence data - Garrett, Karen A.; Gomez-Montano, Lorena; Jumpponen, Ari M. (My University, 2013)
This R script performs statistical analyses using sequence data. It goes through all the steps from reading the data into R, merging multiple datasets, calculating diversity metrics, performing statistical analysis such as linear regression and non-metric multidimensional scaling (NMDS), making graphs and saving and exporting them for use in presentations and publications. It illustrates the analyses used in Gomez-Montano et al. 2013, and can be used as a template for other similar analyses. Sections: 1. Preparing data 2. Diversity metrics 3. Analysis of individual OTU frequencies 4. Soil physical and chemical analyses 5. NMDS community analysis
Citation: Gomez-Montano, L. Jumpponen, A., Gonzales, M., . . . Garrett, K. (2013). Do bacterial and fungal communities in soils of the Bolivian Altiplano change under shorter fallow periods?. Soil Biology & Biochemistry, 65, 50-59. https://doi.org/10.1016/j.soilbio.2013.04.005
Keywords: Bacterial communities; Fungal communities; High-throughput sequencing; Metagenomics; R programming environment; Non-metric multidimensional scaling